IDDF2019-ABS-0082 Microvascular invasion at primary resection guiding the therapeutic options of recurrent intermediate-advanced hepatocellular carcinoma. (June 2019) - Li, Bin; Xiao, Han; Chen, Zebin; Chen, Shuling; Peng, Zhenwei; Kuang, Ming
Abstract : Background: Treatment strategies for recurrent hepatocellular carcinoma (rHCC) are controversial. We used the status of microvascular invasion (MVI) at primary resection as a marker to choose the appropriate treatment options for rHCC patients in Barcelona Clinic Liver Cancer (BCLC) stage B-C. Methods: From Jun 2009 to Jun 2017, a consecutive 241 patients with postsurgical recurrence at BCLC stage B-C who received re-resection (RR), radiofrequency ablation (RFA) or transarterial chemoembolization(TACE), were enrolled. Multivariate COX regression analysis was performed to identify the prognostic factors for post-recurrence survival (PRS). PRS, overall survival (OS) and costs were compared between RR/RFA and TACE according to MVI status. A one-to-one propensity score matching analysis was performed to reduce bias. Results: For MVI(-) patients, the median PRS was 88.1 months for the RR/RFA group (n=20) and 21.1 months for the TACE group (n=49) with the HR=0.40 ( P =0.014). The corresponding OS were 98.1 and 26.6 months, respectively (HR=0.34, P =0.003). For MVI(+) patients, the median PRS in RR/RFA group (n=35) and TACE group (n=137) were 15.9 and 10.7 months, respectively (HR=0.67, P =0.105). The corresponding OS were 23.5 and 16.8 months, respectively (HR=0.66, P =0.087). After matching, the dominance of RR/RFA over TACE remained in MVI(-) patients for both PRS (62.3 vs 18.5 months; HR=0.37, 95%CI=0.15–0.96; P =0.033) and OS (98.1 vs 33.3 months; HR=0.31, P =0.008). No significant difference was found in MVI(+) patients for either PRS (15.9 vs 15.6 months; HR=0.83, 95%CI=0.44–1.55; P =0.554) or OS (23.5 vs 28.1 months; HR=0.90, P =0.752). The cost of TACE group was significant lower than that of the RR/RFA group for both MVI-positive patients ( P =0.007) and MVI-negative patients ( P <0.001). Conclusions: For MVI-negative patients, RR/RFA provided better survival than TACE while for MVI-positive patients, TACE was recommended.